Penerapan Metode Pembelajaran Efektif dalam Pendekatan Layanan Bimbingan Belajar pada Kegiatan PPL di SD Negeri Kandang Panjang 02 - Okpatrioka Okpatrioka; Ginawati Ginawati; Nono Yatno (Lembaga Pengembangan Kinerja Dosen, 2024)
Laziness is a behavior that is often experienced by almost everyone, including students. As the next generation of the nation, students should have high enthusiasm in pursuing knowledge. Education is not only limited to the classroom; knowledge can be found anywhere and anytime. Therefore, it is important for students to try to overcome their lazy habits, because laziness can have detrimental effects. For example, if a student is lazy to study, he will lose the opportunity to gain useful knowledge. On the other hand, if the student is diligent in studying and is able to overcome laziness, they will gain broader knowledge and insight. Problems that often arise are the lack of enthusiasm from students in the learning process, non-compliance in completing assignments and taking notes, and the tendency to fall asleep or leave the classroom during the lesson. To overcome this problem, the method of implementing group guidance is carried out in three stages: First, starting with the introduction and delivery of material on the theme of